Atuação do BNDES de 2002 a 2016: uma visão pós keynesiana - Muniz, Leonardo Joaquim (2018)
The central objective of BNDES disbursement research and analysis from 2002 to 2016, as well as to analyze if the Bank adhered to the post-Keynesian concepts of development bank. The specific objective is to clarify where BNDES funds were directed in the different economic cycles of the period under analysis. And BNDES disbursement prices in relation to payment banks